Effect of a Randomised Controlled Vitamin D Trial on Insulin Resistance and Glucose Metabolism in Patients with Type 2 Diabetes Mellitus - Strobel, F.; Reusch, J.; Penna-Martinez, M.; Ramos-Lopez, E.; Klahold, E.; Klepzig, C.; Wehrle, J.; Kahles, H.; Badenhoop, K. (Hormone and Metabolic Research, 2014)
The aim of our study was to investigate the influence of a 6-month vitamin D supplementation in patients with noninsulin-requiring type 2 diabetes mellitus. We included 86 patients in a placebo-controlled, randomised, double-blind study. During 6 months patients received Vigantol oil once a week corresponding to a daily dose of 1904 IU or placebo oil, followed by 6 months of follow-up. At start and at 3-month intervals 25OHD, PTH, body mass index, HbA1c, insulin, C-peptide, and homeostasis model assessment-index were measured. The primary outcome was a change in fasting blood glucose and insulin levels. After 6 months of therapy, the verum group’s 25OHD had increased to a median of 35 ng/ml in comparison to the placebo group (median 20 ng/ml, p<10−6). PTH tended to decrease in the verum group (25.5 pg/ml vs. 35.0 pg/ml, p=0.08). After 6 months of therapy, 31 patients (78%) achieved a 25OHD concentration of >20 ng/ml. Their HbA1c was significantly lower at baseline (p=0.008) and after therapy (p=0.009) than in patients with 25OHD below 20 ng/ml. C-Peptide, insulin, and HOMA-index did not change significantly in the verum group but fasting insulin was positively correlated with 25OHD concentrations after 6 months of therapy in both groups. There were no significant effects of vitamin D with a daily dose of 1904 IU on metabolic parameters in type 2 diabetes. However, the correlative findings of this study suggest a link of the 25OHD status and metabolic function in type 2 diabetes. Whether vitamin D therapy with higher doses can improve glucose metabolism needs to be investigated in follow-up trials.
Keywords: diabetes; vitamin D; metabolism; HbA1c; C-peptide; insulin